Control Effect of Zinc Fertilizer Application Against Apple Little Leaf - Fanglun, Jin; Shihua, Feng; Ming, Li; Fawei, Zhang; Chengmin, Han; Xuexi, Ao (Plant Diseases and Pests(植物病虫害研究：英文版), 2016)
In order to provide a theoretical basis for apple cultivation techniques and to provide a reference for preparation of scientific management measures,the occurrence and damage status of apple little leaf in northern Guizhou was investigated,and fertilizer control test against the disease was also conducted.（1）Apple little leaf occurred from April to October in apple producing areas in northern Guizhou every year,with heavy incidence from April to May,light incidence from June to July,and the lightest incidence from August to October.（2） Effectiveness test showed that application of zinc sulfate fertilizer 135 g ＋ cow dung 10 kg received the best control effect,followed by zinc sulfate fertilizer 165 g ＋ cow dung 10 kg,then zinc sulfate fertilizer 105 g ＋ cow dung 10 kg and zinc sulfate fertilizer 150 g ＋ cow dung 10 kg.（3） Based on local environmental conditions,occurrence and damage situation,incidence conditions and fertilizer efficacy test,comprehensive prevention and control technology with rational supplement of zinc fertilizer could be used to control apple little leaf.